Sustainability and Depoliticisation: Certifications in the Cut-Flower Industry at Lake Naivasha, Kenya. Issue 3 (December 2017) - Kuiper, Gerda; Gemählich, Andreas
This article focuses on the emergence of certification schemes in the cut-flower industry in Naivasha, Kenya. It is shown that, although this turn is often legitimised through references to "sustainability, " the change was mainly brought about by the growing importance of a new value chain of "direct sales." The article furthermore elaborates on the most well-known certificate in Naivasha, Fairtrade. This certificate aims to enhance sustainability by empowering workers, yet it does not profoundly change power relations within the industry. The article concludes that "sustainability" in the context of Naivasha has been an ill-defined concept, used to legitimise a turn to certifications. Rather than bringing about a profound transformation of the production process, these certifications obscure and even consolidate the existing socio-economic configuration of the industry. Certifications thus run the risk of having "depoliticising" effects.